Analisis Makna Poster Film "Laut Tengah” Karya Berliana Kimberly: Kajian Semiotika Ferdinan De Saussure - Darajati, Aflaha (Maliki Interdisciplinary Journal, 2025)
This study analyzes the symbolic meaning in the movie poster “Laut Tengah” by Berliana Kimberly using Ferdinand de Saussure’s semiotic theory. This poster was chosen because its visual elements contain explicit and implicit symbolic messages about a love story intertwined with education. In Saussure’s theory, a sign consists of two components: the signifier as the physical form of the sign, and the signified as the concept or idea contained within it. A qualitative descriptive research method was used to identify the elements of the poster based on Miles and Huberman’s technique, namely data collection, reduction, presentation, and conclusion drawing. The results of the analysis show that this poster successfully conveys the themes of love, dreams, and destiny through a combination of visual elements such as character expressions, the South Korean background, and the words “Takdir Cinta” (Destiny of Love). This study shows how visual communication design can build audience curiosity and interest in films.